Lower limb maximal power predicts punching speed in different static and dynamic attacking techniques in karate - Quinzi, F.; Rosellini, G.; Sbriccoli, P. (The Journal of Strength and Conditioning Research, 2022)
Punching performance of karate can be predicted from lower limb maximal power. However, this relationship was observed only in single actions starting from a static position, thus calling for an investigation on the applicability of this relationship to other conditions. This study aims at investigating whether the relationship between lower limb maximal power and punch speed holds true, not only for single actions, but also for a combination of upper limb techniques in static and dynamic conditions. Ten national-level karate athletes aged 22.3 ± 1.8 years were assessed for maximal power of upper and lower limbs during a bench press and a back squat, and for punching speed during 2 punching techniques (gyaku tsuki [GT]; kizami tsuki and gyaku tsuki [KG]) starting from a static (GTS; KGS) or a dynamic (GTD; KGD) condition. Pearson's correlations were obtained between upper and lower limb maximal relative power and punch speed across tasks and conditions. Significance level was set at p < 0.05. Significant correlations were observed between lower limb maximal relative power and punch speed for all tasks and conditions (r = 0.66-0.80; p = 0.005-0.037). The present results further our knowledge on the relationship between lower limb maximal power and punch speed showing that this relationship holds true also for combinations of punching techniques performed also in dynamic conditions. This information can be useful for karate trainers to predict the punching performance of their athletes using a simple test to assess maximal lower limb power.